Extramammary Paget Disease of Peristomal Skin Secondary to Bladder Urothelial Carcinoma - Victoria Dukharan; Adriana L Della Porta; Scott Gregory; Gulsun Erdag (European Medical Journal)
Extramammary Paget disease (EMPD) is a rare, cutaneous condition, which can present secondary to underlying carcinoma as an eczematoid rash that often mimics other conditions. Secondary EMPD should, therefore, be considered in the differential diagnosis where there is potential for malignant extension, particularly in post-operative tissue. This report describes a case of secondary EMPD of the peristomal skin in a patient with a distant history of cystectomy with ileal conduit for urothelial carcinoma, who developed an extensive eczematoid rash over 5 years after attempting several ineffective treatments. Early dermatologic referral for persistent inflammatory cutaneous disorders and appropriate histopathologic testing may reduce delays in the diagnosis of EMPD.